Optimasi Pengelolaan Waduk Pondok Ngawi Jawa Timur - Hendro Susilo (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
Pondok Reservoir is one of the smaller reservoirs built in Bengawan Solo River Basin, located in Kali Dero, Gandong Village, Bringin District, Ngawi District, with a puddle of 3.6 km2 and 32.9 km2 of drainage area. The total reservoir volume is 25,233 MCM and the effective dams volume is 22,333 MCM. The reservoirs are used to irrigate 3.596 Ha of irrigated rice fields which are distributed through four weirs, namely Dero weir, Sambiroto dam, Plesungan dam, and Padas dam. The results showed that selected crops were rice and maize, while to obtain maximum annual agricultural benefit benefit can be done with the initial period of planting for the first planting season is the third week of November, which has annual net benefit value of agriculture of Rp. 10,797,000,000. Through continuous water supply, the optimal planting area for each planting season is the first planting season in the third week of November with rice plant of 2877 ha and 719 ha of maize; the second growing season in the third week of March with rice plants 1216 ha and 1216 ha of maize; third planting season in the third week of July with 402 ha of corn. Percentage of planted area from available land per planting season is: first planting season is 100%, second planting season is 67,63% and planting season is 11,18%, so planting intensity is 178,8%.